DLL3 expression is a predictive marker of sensitivity to adjuvant chemotherapy for pulmonary LCNEC. Issue 9 (21st July 2020) - Ogawa, Hiroyuki; Sakai, Yasuhiro; Nishio, Wataru; Fujibayashi, Yusuke; Nishikubo, Megumi; Nishioka, Yuki; Tane, Shinya; Kitamura, Yoshitaka; Sudo, Tamotsu; Sakuma, Toshiko; Yoshimura, Masahiro
Abstract : Background: The mammalian Notch family ligands delta‐like 3 (DLL3) is reported to be a potential therapeutic target for large cell neuroendocrine carcinomas (LCNEC). The effect of DLL3 expression on LCNEC prognosis has not yet been elucidated. Methods: We reviewed the medical records of 70 LCNEC patients undergoing surgical resection between 2001 and 2015 using a prospectively maintained database. We performed immunohistochemistry for DLL3 and investigated the correlation between the sensitivity of LCNEC to platinum‐based adjuvant chemotherapy. Results: DLL3 expression was positive in 26 (37.1%) LCNEC patients. A total of 23 patients (32.9%) received platinum‐based adjuvant chemotherapy. Among patients with DLL3 expression‐positive tumors, no difference was found in the five‐year overall survival (OS) or recurrence‐free survival (RFS) between patients with and without adjuvant chemotherapy (surgery + chemotherapy vs. surgery alone, five‐year OS: 58.3% vs. 35.7% P = 0.36, five‐year RFS: 41.7% vs. 35.7% P = 0.74). In contrast, among patients with DLL3‐negative tumors, significantly greater five‐year OS and RFS rates were observed for patients with adjuvant chemotherapy than for those without it (surgery + chemotherapy vs. surgery alone: five‐year OS: 90.0% vs. 26.9% P <0.01, five‐year RFS: 80.0% vs. 21.7% P  < 0.01). A multivariate analysis for the RFS revealed that adjuvant chemotherapy was a significant independent prognostic factor among patients with DLL3‐negative tumors (hazard ratio [HR]: 0.05, 95% confidence interval [CI]: 0.01–0.41, P < 0.01), although it was not a factor among patients with DLL3‐positive tumors (HR: 0.73, 95% CI: 0.23–2.27, P = 0.58). Conclusions: Our results revealed that DLL3 is a predictive marker of sensitivity to platinum‐based adjuvant chemotherapy for LCNEC. Key points: Significant findings of the study: DLL3 was a predictive marker of sensitivity to platinum‐based adjuvant chemotherapy for LCNEC. Among patients with DLL3 expression‐negative LCNEC, platinum‐based adjuvant chemotherapy significantly improved the OS and RFS, although it did not do so among patients with DLL3 expression‐positive LCNEC. What this study adds: Our results suggest that DLL3 expression‐positive LCNEC may be better treated with other types of adjuvant chemotherapy, such as the anti‐DLL3 therapies if these effects are confirmed by ongoing clinical research. Abstract : DLL3 was a predictive marker of sensitivity to platinum‐based adjuvant chemotherapy for LCNEC. Among patients with DLL3 expression‐negative LCNEC, platinum‐based adjuvant chemotherapy significantly improved the OS and RFS, although it did not do so among patients with DLL3 expression‐positive LCNEC.